Easy and visible: accountability of the Gontor modern islamic boarding school - Wijaya, Riesanti Edie; Azizah, Salma Marlida (Manajemen dan Bisnis, 2026)
Accountability is essential for all organizations, including faith-based organizations (FBOs). Stakeholders require accountability information to assess how management operates the organization. Since organizational accountability is shaped by culture and local wisdom, its form varies significantly across communities. This study explores accountability concepts within the financial management framework of Gontor Modern Islamic Boarding School (GMIBS). Adopting an interpretive paradigm, researchers conducted in-depth interviews with key informants—financial report preparers with comprehensive understanding of institutional financial reporting. Two additional informants obtained through snowball sampling enabled data triangulation. Thematic analysis was employed to analyze the collected data. The findings reveal a unique accountability concept tailored to GMIBS's conditions and culture, built upon four principles: transparency, easy data access, openness, and globalization. These principles underlie financial reporting in two categories: vertical and downward accountability. Vertical accountability focuses on the Waqf Council; given members' relatively older age, reports are simplified for easier comprehension without requiring advanced software. Downward accountability addresses other stakeholders' needs, allowing them to directly observe and assess property improvements through their senses. This study demonstrates that accountability is socially constructed, and the unique accountability practices in GMIBS contribute to the literature on accountability in faith-based organizations.